Pharmacokinetics of difloxacin in Sichuan Shelducks after single or multiple dosing - Yang-Guang Jin; Fang Yang; Yu-Rong Yang; Yue Liu; Yan-Ni Zhang; Yu-Xin Chen; Long-Ji Sun; Shi-Hao Li; Wen-Rui Wang; Fan Yang; Xing-Ping Li (Poultry Science, 2025)
This study evaluated both single and multiple dosing regimens of difloxacin administered via different routes to Sichuan Shelducks: single intramuscular (sIM), intravenous (sIV), oral gavage (sPO), and multiple intramuscular (mIM) and oral gavage (mPO) administrations. The sIV, sPO, and sIM groups received a single dose of difloxacin at 10 mg/kg body weight (BW). The mPO and mIM groups received multiple doses of 10 mg/kg BW at 12-hour intervals: the mPO group received 10 oral doses, and the mIM group received 6 intramuscular doses. Blood samples were collected at various time points from 0 to 48 hours, and plasma concentrations of difloxacin were analyzed using a validated high-performance liquid chromatography (HPLC) method. Pharmacokinetic parameters were calculated using Phoenix software and non-compartmental analysis (NCA). The peak plasma concentration (Cmax) values were 2.05 ± 0.60, 2.26 ± 0.36, 2.81 ± 0.92, and 3.42 ± 0.59 μg/mL for the sPO, sIM, mPO, and mIM groups, respectively, with corresponding peak time (tmax) of 0.75 ± 0.17, 0.77 ± 0.26, 0.96 ± 0.61, and 0.65 ± 0.33 hours. The PO and IM bioavailability (F) after single administration were 96.00 % ± 22.03 % and 87.62 % ± 9.81 %, respectively. Following single IV administration, difloxacin exhibited extensive distribution, with a volume of distribution (VZ) of 6.12 ± 3.59 L/kg and a steady-state volume of distribution (VSS) of 3.18 ± 1.09 L/kg. Difloxacin was eliminated slowly, with terminal half-lives (t1/2λz) of 10.77 ± 1.78, 4.53 ± 4.44, 4.53 ± 2.97, 6.00 ± 2.00, and 5.33 ± 4.35 hours in the sPO, sIM, sIV, mPO, and mIM groups, respectively. Based on the AUC/MIC ratios, the current single IV and PO dosing regimens, as well as the multiple IM and PO regimens, appear effective against pathogens with MIC values ≤ 0.1 μg/mL. However, the single IM dose of 10 mg/kg BW may be inadequate for treating infections caused by organisms with MIC values > 0.1 μg/mL.